Monitoring and temperature control system for fish farming in an IOT-based bucket using an android application - Yazid, Abdul; Kusumawati, Weny Indah; Harianto; Susanto, Pauladie (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This study seeks to create and implement an Internet of Things (IoT)-based system for monitoring and controlling temperature in fish farming within a bucket (Budikdamber) using temperature sensors. The main focus is to set the optimal temperature range for catfish farming in the Budikdamber, ensuring environmental conditions that suit the needs of catfish. Automatic controls are integrated to keep the water temperature in the bucket within the desired range. The system is also capable of automatically activating or deactivating devices such as the Peltier, lights, filling pump, and draining pump to achieve the appropriate temperature. In the test using a 50-litre bucket, a thorough evaluation and testing showed that the DS18B20 temperature sensor had an error rate of 0.8826%, while the Ultrasonic sensor had an error rate of 0.737%. Nonetheless, the other components in the device operate optimally with performance levels reaching 100%, according to their functions. Testing of the Android App on this device achieved an accuracy rate of 100%, indicating that this device can be effectively monitored and controlled remotely through the Android App. The conclusion of this research provides insight into the performance of temperature sensors, system optimization, and the effectiveness of remote control using Android Apps in the context of fish farming.